2015
DOI: 10.17554/j.issn.2311-5106.2015.02.63
|View full text |Cite
|
Sign up to set email alerts
|

Philos Plate in Proximal Humerus Fracture–Its Functional Outcome and Complications

Abstract: AIM:Technique for the fixation of two, three, and four part proximal humerus fractures has rapidly shifted towards the use of locking plates. The objective of this prospective study was to evaluate functional outcome and complications of proximal humeral fractures managed with proximal humerus internal locking system (PHILOS). METHODS: 16 men and 9 women aged 19 to 82 (mean, 49.24) with an acute proximal humerus fracture were treated with PHILOS plate by using deltopectoral approach. Outcome measurements inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 21 publications
6
9
0
Order By: Relevance
“…In the study by Kumar GK et al, [12], at the final follow-up the mean Constant-Murley score was 79 (range 50-100) and the results were excellent in 25 patients, good in 13 patients, fair in 6 patients and poor in 5 patient. Out of 30 cases, excellent result in 7 cases, Good in16 cases Satisfactory in 5 cases and Poor in 2 cases were reported by Sreen S et al, [13] and outcomes were excellent in 16%, good in 44%, fair in 16% while poor in 24% in the study done by Bansal V et al, [15].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In the study by Kumar GK et al, [12], at the final follow-up the mean Constant-Murley score was 79 (range 50-100) and the results were excellent in 25 patients, good in 13 patients, fair in 6 patients and poor in 5 patient. Out of 30 cases, excellent result in 7 cases, Good in16 cases Satisfactory in 5 cases and Poor in 2 cases were reported by Sreen S et al, [13] and outcomes were excellent in 16%, good in 44%, fair in 16% while poor in 24% in the study done by Bansal V et al, [15].…”
Section: Discussionmentioning
confidence: 78%
“…of patients in this study was 44.0333 ± 11.2449 years, range (21-65 years. The average age incidence was 54.3±5.8 years in the study done by Doshi C et al, [11] and 38 years (range 24-68) in the study done by Kumar GK et al, [12] 58 years(range 22-78) in the study done by Sreen S et al, [13] 49.24 years in the study done by Bansal V et al, [15].…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, 20% of cases had excellent functional outcome, 30% cases had good functional outcome, 35% of cases had fair functional outcome and 15% cases had poor functional outcome (Table 3). A study by Vivek Bansal et al found excellent outcome in 16% cases, good outcome in 44% cases, fair in 16% cases and poor outcome in 24% cases [9]. The functional outcome was excellent in 15 cases, good in 7 cases, fair in 5 cases and poor in 4 cases [10] .…”
Section: Resultsmentioning
confidence: 94%
“…[8] . A study by Vivek Bansal et al included 25 cases with acute proximal humerus fractures to assess the functional outcome in these cases managed with PHILOS plate noticed a mean constant score after 6 months follow up was 57.4 and the constant score was poor in cases with 4 part fractures [9] . A study by Goutam Kumar Satpathy and Dillip Kumar Chand recruited 31 cases with proximal humerus fractures managed with PHILOS plate noticed a mean constant murley score at the final follow up was 81 (range 57-100) [10] .…”
Section: Methodsmentioning
confidence: 99%
“…Some risk factors of complications suggested by the authors include a non-anatomical reduction, medial cortical bone deficit, fixation using a short locking screw at the humeral head, and inappropriate fixation of the greater tuberosity. Bansal et al 14) reported the functional outcomes, in terms of the Constant score, and the postoperative complications after internal fixation using LCPs for proximal humeral fractures in 25 patients. At the 6-month follow-up, the average Constant score was 57.4, showing a generally favorable outcome in patients ("excellent" in 4 patients [16%]; "good" in 11 patients [44%]; "fair" in 4 patients [16%]; and "poor" in 6 patients [24%]).…”
Section: A B Cmentioning
confidence: 99%